2016
DOI: 10.3390/systems4040038
|View full text |Cite
|
Sign up to set email alerts
|

Designing Computer-Supported Complex Systems Curricula for the Next Generation Science Standards in High School Science Classrooms

Abstract: We present a curriculum and instruction framework for computer-supported teaching and learning about complex systems in high school science classrooms. This work responds to a need in K-12 science education research and practice for the articulation of design features for classroom instruction that can address the Next Generation Science Standards (NGSS) recently launched in the USA. We outline the features of the framework, including curricular relevance, cognitively rich pedagogies, computational tools for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…A number of studies (e.g., Klopfer, Yoon, & Perry, 2005; Repenning et al, 2015; Vattam et al, 2011; Wilensky & Reisman, 2006; Yoon, Koehler-Yom, Anderson, Lin, & Klopfer, 2015) describe computational tools that have been developed to visualize structures and mechanisms that enable users to view the evolution of systems over time. A particularly robust line of research has been aimed at developing agent-based simulations represented in modeling tools such as NetLogo (Wilensky & Reisman, 2006) and StarLogo (Yoon et al, 2016). These simulations allow students to manipulate and construct facsimiles of scientific systems in which changes in initial conditions, random variation, decentralized interactions, and self-organized emergent behaviors (among other system characteristics) are investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (e.g., Klopfer, Yoon, & Perry, 2005; Repenning et al, 2015; Vattam et al, 2011; Wilensky & Reisman, 2006; Yoon, Koehler-Yom, Anderson, Lin, & Klopfer, 2015) describe computational tools that have been developed to visualize structures and mechanisms that enable users to view the evolution of systems over time. A particularly robust line of research has been aimed at developing agent-based simulations represented in modeling tools such as NetLogo (Wilensky & Reisman, 2006) and StarLogo (Yoon et al, 2016). These simulations allow students to manipulate and construct facsimiles of scientific systems in which changes in initial conditions, random variation, decentralized interactions, and self-organized emergent behaviors (among other system characteristics) are investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier designs for learning science with a complex systems perspective implemented the computational ABM. Such designs have demonstrated important advantages to learning through a complexity approach to support conceptual change in several scientific domains [(Holbert & Wilensky, ; Levy & Wilensky, ) in chemistry; (Brady et al, ) in physics; (Dickes, Sengupta, Farris, & Basu, ; Yoon et al, ; Wilkerson‐Jerde et al, ) in biology; (Blikstein & Wilensky, 2009; Jacobson et al, ) in materials science; (Levy & Mioduser, ) in robotics], or in systems thinking as a more general form of reasoning (Rates et al, ). Learning through this approach focuses on entities and their actions, such as movement, interactions, and global flows, and allows students to comprehend parallel processes by which emergent phenomena form.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Users can then compare the code to the visualization of the system on the screen as it is running in real time. Research using such agent-based modeling tools has shown that the ability to study the code while visualizing the system, in addition to the ability to observe systems processes as they emerge over time, creates far deeper meaning for users than when learning from static images [4,5]. StarLogo also allows users to manipulate system variables to create different initial conditions, modify interactional states and agent characteristics, and adjust how fast or slow or specify the period of time that the simulation runs in order to experiment with the tool.…”
mentioning
confidence: 99%